Local Memory and Urban Space - Łupienko, Aleksander (1980– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The paper ponders over the issue of memory and urban space. It shows how these categories have been discussed in the literature and how they are connected to the problem of place identity. The paper also highlights the need to appreciate and assess the physical aspect of objects, which act as memory markers in the urban space. The author argues that what is being memorialised and conveyed as meaning is the past lived experience. As a case in point, two memory acts are analysed in the paper, clearly showing the interdependence of various temporalities in the anniversary celebrations. In the festivities celebrating the 100th (in 1881) and 150th (in 1931/2) anniversaries of the consecration of the Lutheran church in Warsaw, the capital of the Kingdom of Poland in the Russian partition and later the capital of a resurrected independent Polish state after 1918, the different present-oriented needs were mirrored in the narratives and commemorations of the past. Idiosyncratic visions of the past help make the small and vulnerable community of Lutherans in an otherwise primarily Roman Catholic environment more coherent, as its members may lay claim to history and construct and stabilise their identification process as descendants of past generations. Moreover, the material fabric of the church seems to be an indispensable factor. The parishioners’ lived experience appears to be a crucial component of commemorations in the late nineteenth and early twentieth centuries.
s. 5-28
Keywords: pamięć; przestrzeń miejska; Kościół ewangelicko-augsburski -- Polska -- Warszawa [KABA]; Luteranie -- Polska -- Warszawa [KABA]

Memory of the Past in the Multi-Ethnic Space of Danube Cities - Tsyganenko, Liliia; Oleinikova, Galina (Instytut Historii Polskiej Akademii Nauk, 2022)
The article presents the issues of preserving the historical memory of the cities of Southern Bessarabia (the southwestern part of Odesa region, Ukraine). The specific features of the region’s historical development, frequent changes in the state affiliation, intermixture and diversity of confessional and ethnographic aspects contributed to the formation of a special, multicultural and polyethnic habitat for the residents of this region. The region’s cities, formed many centuries ago, demonstrate specific, often unique features of the memory of the past, embodied in the temples, street names, residential buildings, and administrative and fortification structures. The preservation of the urban memory and its popularisation serve as the foundation of human beings who are free from prejudice, protect their identity and are tolerant of their neighbours.
s. 29-48
Keywords: Besarabia Południowa; Pamięć zbiorowa [KABA]; miasta; pomniki; kościoły; meczety

The General Procurators of the Teutonic Order Towards the Polish-Teutonic Conflict - Bar, Přemysl (1979– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The article deals with the activities of the General Procurators of the Teutonic Order regarding the Polish-Teutonic dispute in the first thirty years of the fifteenth century. Based on their dispatches sent to Marienburg, it can be assumed that the Procurators were not passive executors of the Grand Master’s orders. Their frequently occurring disagreements resulted not only from their distinctive personal qualities but also from their different perspectives on assessing what was in the best interest of the Teutonic Order. The Grand Masters lacked professional knowledge not only of law (especially canon law) but also of how the Roman curia functioned.
s. 181-205
Keywords: Państwo Krzyżackie -- stosunki -- Polska -- 15 w. [KABA]; Polska -- stosunki -- Państwo Krzyżackie -- 15 w. [KABA]; Ordo Fratrum Domus Hospitalis Sanctae Mariae Teutonicorum in Jerusalem -- 15 w. [KABA]; Sobór w Konstancji (1414-1418) [KABA]; Sobór Bazylejski (1431-1449) [KABA]; Prokuratorzy generalni; Kuria Rzymska

The Mennonites’ ‘Great Trek’ from the Occupied Regions of Ukraine to Warthegau in 1943–4 - Martynenko, Volodymyr; Venger, Nataliya (Instytut Historii Polskiej Akademii Nauk, 2022)
The German troops’ large-scale retreat on the Eastern Front was accompanied by a substantial population outflow from the occupied regions of the USSR. The German Mennonites (approx. 35,000 people) preferred to obey the occupiers’ order and evacuate to the west in the autumn of 1943. Several thousands of them were transported in echelons directly to Warthegau and the region of Danzig. The remaining part of deportees had to sustain a difficult and dramatic route in the convoys. The Nazi leadership planned to use them as settlers or labour force on the annexed Western Polish lands. After the end of the Second World War, most of the Mennonites were forcibly repatriated to the USSR; others succeeded in emigrating to Canada or Latin America.
s. 207-237
Keywords: Mennonici [KABA]; uchodźcy; ewakuacja z Ukrainy; Trzecia Rzesza; Urząd do spraw Mniejszości Niemieckiej; Volksdeutsche [KABA]; Ziemie Zachodnie i Północne (Polska) [KABA]

Shifting Borders – Shifting Languages: Investigating Commemorative Cityscape in Poznań and Słubice - Fabiszak, Małgorzata; Brzezińska, Anna Weronika; Dobkiewicz, Patryk (Instytut Historii Polskiej Akademii Nauk, 2022)
This article explores patterns of street renaming in two locations which over the last century were interchangeably controlled by Germany and Poland: Posen/Poznań and Dammvorstadt/Słubice. It examines how changes in the language of administration influenced their urban streetscape. The results demonstrate that there are several different semantic categories of street names which show varied affinity to change. Commemorative street names inscribing personal names are most prone to alteration, while those based on topology and landmarks are often translated from one language to another and retain their meaning. Street names based on place names are a heterogeneous category with directional names showing more stability than those which represent the national geographical imagery.
s. 277-299
Keywords: Polska -- historia -- czasopisma [KABA]

Acta Poloniae Historica T. 126 (2022), Reviews - Piotrowski, Igor; Korczak-Siedlecka, Jaśmina; Grata, Paweł; Lis, Tomasz Jacek (1988– ); Mieszkowski, Łukasz; Rembacka, Katarzyna (1974– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
s. 239-276
Keywords: Polska -- historia -- czasopisma [KABA]

Inconveniences of Memory : The Monument to the Soviet Army and Georgi Dimitrov’s Mausoleum in Sofia after 1989 - Decheva, Daniela (Instytut Historii Polskiej Akademii Nauk, 2022)
The paper discusses the transformations of memory caused by the preservation, removal or redefinition of memorials. These transformations indicate the competition between political and ideological views in Bulgarian society after 1989. Two cases are analysed: the deconstruction of Georgi Dimitrov’s already-empty mausoleum in 1999 and the Monument to the Soviet Army, still standing in Sofia. Both instances are significant indicators of power constellations, which, in the second case, also have a precise foreign policy dimension (relations with Russia). The periodically activated debates, especially concerning the Monument to the Soviet Army, indicate the absence of a coherent memory policy and general ambiguous attitudes in Bulgarian society towards the communist past.
p. 89-100
Keywords: Pamięć zbiorowa [KABA]; Pamięć zbiorowa -- aspekt polityczny [KABA]; Komunizm -- Bułgaria [KABA]; Bułgaria -- 1990- [KABA]; przeszłość komunistyczna; Mauzoleum Georgiego Dimitrowa w Sofii; pomnik Armii Czerwonej w Sofii

Reorganisation of the ‘Polish’ Space of Lviv as a Component of the Process of City Space Identity Reconstruction after 1991 - Szczepański, Jan (Instytut Historii Polskiej Akademii Nauk, 2022)
The article describes the process of the reconstruction and protection of the Polish minority and Polish heritage in Lviv after 1991. This process is presented in the context of Polish-Ukrainian relations. The author indicates the most important actors in this process, focusing on presenting this phenomenon in spatial terms. Next, he describes achievements and possibilities for further development, in addition to the causes and effects of the phenomenon.
s. 101-122
Keywords: Lwów (Ukraina) -- 1990- [KABA]; Polacy -- Ukraina -- Lwów -- 1990- [KABA]; Polska -- stosunki -- Ukraina -- 1990- [KABA]; Ukraina -- stosunki -- Polska -- 1990- [KABA]; Postkomunizm [KABA]; dziedzictwo; społeczeństwo

Commemoration of the 1905 Revolution in the Industrial City : The Case of Łódź - Śmiechowski, Kamil (1985– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The article discusses the current practices of commemorating the 1905 revolution in Łódź. The changes taking place in the city’s memory policy are conditioned both by the loss of memory of the events from a century ago and by changing political factors in the post-transformation period. The city is a paradigmatic example of a post-industrial city in Central and Eastern Europe facing an identity crisis. Narratives formulated ‘from above’ compete with those created ‘from below’. While the former are based on the construction of a utopian, capitalist city of success, the latter claim the history of the people of Łódź. Revitalising the memory of the Revolution of 1905 plays a key role in these negotiations, contributing to a revision of the post-transformation amnesia about the city’s working-class past
s. 67-87
Keywords: Łódź (Polska) -- historia [KABA]; Polska -- 1905-1907 (Rewolucja) [KABA]; Pamięć zbiorowa -- Polska [KABA]; Pamięć zbiorowa -- aspekt polityczny [KABA]; Upamiętnianie -- Polska -- 1945- [KABA]; Ruchy społeczne -- Polska -- 20 w. [KABA]; ruchy miejskie

Acta Poloniae Historica T. 126 (2022), Title page, Contents, Contributors - Instytut Historii Polskiej Akademii Nauk (Instytut Historii Polskiej Akademii Nauk, 2022)
s. 1-4, 301-302
Keywords: Polska -- historia -- czasopisma [KABA]

Was There Ever a Polish Peasant? Historical Imagination and the People’s History of Poland - Mazur, Zachary (Instytut Historii Polskiej Akademii Nauk, 2022)
This essay uses five new Polish-language books popularising the ‘people’s’ history perspective as a jumping-off point to discuss distortions in the historical imagination. At the centre is the issue of the peasantry. In some national mythologies, the peasants or the ‘people’ serve as the heart of the nation. In the Polish case, this has been the role of the nobility or szlachta and as a result the peasants are often forgotten or skipped over in popular historical narratives. These new books represent a sea change in historical imagination, not for the academy, but for the broader public.
s. 155-180
Keywords: Nacjonalizm [KABA]; Chłopi -- Polska -- postawy -- 19 w. [KABA]; Chłopi -- Polska -- postawy -- 20 w. [KABA]; szlachta; pamięć; historiografia

Research on the Cities of Pre-Partition Poland in the Last Decade (Trends, Achievements, Perspectives): Bibliographical Survey - Okniński, Piotr (1989– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
The article contains a synthetic review of the most important subjects and directions of research in the field of the history of cities and townspeople in pre-partition Poland (to the end of the eighteenth century) based on scholarly publications from the last ten years. The author characterises the attitude of contemporary historians of cities towards questionnaires and research methods worked out in the second half of the twentieth century in the area of socio-economic history. He also outlines the prospects for the further development of Polish urban historiography, emphasising the importance of taking inspiration from the achievements of cultural anthropology and the cooperation of historians with representatives of other humanistic disciplines.
s. 143-154
Keywords: miasta; Ludność miejska [KABA]; kultura miejska; metodologia badań historycznych; historia historiografii; Marksizm

Private Memory in Public Space - Grzeszczuk-Brendel, Hanna (Instytut Historii Polskiej Akademii Nauk, 2022)
Commemoration in public space is usually associated with the creation of official objects related to important events or individuals, most often in the form of monuments or plaques. In the paper, the author considers alternative forms of commemoration which, by existing in the social space, invade privacy, taking into account not only artistic activities such as Stolpersteine/Gunter Demnig’s “stumbling stones” but also, for example, candles or flowers at accident sites. So, the author examines non-monumental forms of commemoration and considers the questions related to the reception of these objects, including their penetration into common cultural spaces.
s. 123-142
Keywords: Pomniki [KABA]; Pamięć (filozofia) [KABA]; Pamięć -- aspekt społeczny [KABA]; Urazy psychiczne -- aspekt społeczny [KABA]; indywidualizacja zmarłych

Deosmanisation of Bosnia and Herzegovina between 1878 and 1918 on the Example of Sarajevo - Lis, Tomasz Jacek (1988– ) (Instytut Historii Polskiej Akademii Nauk, 2022)
In 1878, Austria-Hungary received a mandate in Berlin to exercise power in Bosnia and Herzegovina. During this period, they pursued a policy of deosmanisation and Europeanisation of the country. Vienna’s actions, however, differed significantly from the policies of neighbouring Serbia or Bulgaria, where the deosmanisation processes resulted in the partial or complete elimination of Islamic culture from the public space. Therefore, the article aims to outline the cultural policy of Austria-Hungary in Bosnia and Herzegovina, primarily in the context of the culture of remembrance, and to show the Austrian visions of the approach to the local past. The capital city of Sarajevo served as an example of this policy, where the processes mentioned above are best seen in terms of the actions of the authorities themselves, the preserved archival legacy, and professional literature.
s. 49-66
Keywords: Pamięć zbiorowa [KABA]; kultura pamięci; Bośnia i Hercegowina -- 1878-1918 [KABA]; Bałkany (region) -- 1870-1914 [KABA]; Austro-Węgry -- polityka i rządy [KABA]